Infectious agents present in monk parakeet (Myiopsitta monachus) and rose-ringed parakeet (Psittacula krameri) invasive species in the parks of Madrid and Seville, Spain - López, Juan; Mogedas, María; Ballesteros, Carlos; Martín-Maldonado, Bárbara; Sacristán, Irene; García, Raúl; Ortiz, Juan Carlos; Esperón, Fernando (Frontiers in Veterinary Science, 2023)
Introduccion.The introduction of invasive species in an ecosystem could lead into a biodiversity loss and the spread of infectious agents which could cause reemergent or emergent zoonotic diseases. Monk parakeet (Myiopsitta monachus) and Rose-ringed parakeet (Psittacula krameri) are considered widespread invasive exotic species in urban habitats from Iberian Peninsula. The aim of this study was to assess the presence of relevant infectious agents in wild parakeets captured in urban parks from Madrid and Seville (Spain). Methods. A total of 81 cloacal samples were collected and analysed by molecular technics. Results. The prevalence of infectious agents varied between parakeet species: 9.5% of monk parakeets and 15% of rosed-ringed parakeets were positive to enteropathogenic E. coli (EPEC); 13.3% of rose-ringed parakeet to avian influenza virus (AIV); 3.3% of rosed-ringed parakeet to Newcastle disease virus (NDV); and a 23.8% of in monk parakeets to Chlamydia psittaci. Discussion. All C. psittaci identified isolates were classified as B, E or E/B genotypes, point towards transmission from wild urban pigeons to parakeets. These results highlight the need of monitoring in parakeet populations, due to the implications human and animal health.